UTILIZATION OF LOCAL WISDOM TO DEVELOP MEAT TOURISM VILLAGE OF TOBA REGENCY THROUGH DIGITAL MARKETING-BASED TOURISM PROMOTION - Jerry Wilson (Jurnal Scientia, 2023)
Pure local wisdom is very well maintained as an attraction for a village area that can provide added value for people who come from that area. Because the results of the community's wisdom provide knowledge for humans to be able to survive and end human activities which can also be an original attraction originating from the area. Therefore this local wisdom must be maintained and cannot be tampered with or tampered with. So this local wisdom can maintain the natural authenticity of a region. Tourism promotion is very much needed in order to call and market a tourist area. This is necessary because tourism promotion is related to selling an interesting and fun tourism product to potential consumers, namely tourists who want to come to visit that location. Of course the prices, places, products sold and the tourist facilities offered can arouse the appetite of guests to be able to come to these tourist attractions. This communication aims to disseminate information, influence and remind the market and products offered by the company so that people want to buy, accept and be loyal to the products offered. The development of tourism marketing that relies on radio television services has long been carried out by companies providing products to consumers by providing radio and television advertisements. And these radio and television advertising activities have had a positive impact on the progress of advertising to date. However, in this case a fairly high cost is needed to carry out promotions using radio and television. Therefore, other effective online media are needed to market a tourism product. The media is currently being developed and the message is to use social media such as YouTube, Facebook, Instagram and TikTok which are promotional platforms which are also quite effective. We call this type of Platform as Digital Media. One of the tourist villages that will be given attention by researchers in this case is the Meat Tourism Village, Tampahan District where the tourist village of Meat is located in Toba district with its beautiful landscape. In this case, what factors are needed to develop a meat touristm village by utilizing local wisdom and culture through digital marketing for tourism business. The results of the analysis from the research conducted by the author that Variable (X1) Local Wisdom, Variable (X2) Benefits of Tourism Villages, Variable (X3) Tourism Promotion and Variable (X4) Utilization of Digital Marketing greatly influence Variable (Y) Development of Tourism Villages. This can be seen from the F test in the SPSS application to find out the Hypothesis of the Independent Variables X1, X2, X3, and X4 affecting the Dependent Variable (Y) where the Sig value is 0.000 <0.002 and the calculated F value is 18.598 > from the F value Table 2.467 so that it can be The conclusion is that all hypotheses (Variable X) are simultaneously acceptable.